CHARACTERIZATION OF (Mg0.5ZN0.5)TiO3 CERAMICS AS MATERIAL CANDIDATES FOR DIELECTRIC RESONATOR AT MICROWAVE FREQUENCY - Mugni Muammar, Asep; Ulfah Ermawati, Frida (Indonesian Physical Review, 2022)
MgTiO3 ceramic is one of the dielectric materials used as a signal generator (dielectric resonator) in microwave telecommunication devices. This research is intended to explore the possibility of a new composition of MgTiO3-based ceramic, i.e. (Mg0.5Zn0.5)TiO3 (abbreviated MZT05) as a dielectric resonator material. The aim was to characterize the resonant frequency of the ceramics on the microwaves (measured using spectrum analyzer), and the results were correlated to structure (X-Ray Diffraction, XRD), microstructure (Scanning Electron Microscope, SEM), and bulk density data (Archimedes method) of the ceramics. The work was begun by compacting the MZT05 crystalline powder in a cylindrical shape with a diameter of 5 mm using a uniaxial die press to produce tablets. The tablets were sintered at 1300 ÂºC with variations holding times of 6, 8, and 10 h to produce ceramics. The structural data revealed that the MgTiO3 phase was identified as the main ceramics, i.e. (96.32-98.70) %molar. The bulk density increased with increasing sinter holding time, from 2.75 g/cm3 (6 h), 2.84 g/cm3 (8 h) to 2.99 g/cm3 (10 h) due to the increase in grain size diameter from 919.75 nm (6 h), 1090.62 nm (8 h) to 1180.72 nm (10 h) accompanied by a decrease in the size of the pore diameter from 924.14 nm (6 h), 917.05 nm (8 h) to 800.22 nm (10 h). The ceramics produced resonant frequencies of 5.07â€“5.08 GHz, which implies that the ceramics are proven to be potential candidates for dielectric resonator materials at microwave frequencies, especially at 5.07-5.08 GHz. The varying sinter holding time seems not to influence the resonant frequency of the ceramics because the variation holding times produce similar resonant frequencies.